The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.amsu.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of serum lipid profiles in patients with and without gallstones: A prospective cross-sectional study

Abstract: Objectives Gallbladder disease is one of the most common diseases of the gastrointestinal tract. Various studies have shown an association between gallstones and an alteration in the serum lipids. The objective of this study was to compare serum lipid profile of gallstone patients with the controls. Methods This prospective cross-sectional study was conducted in the Surgical Department of the Services Institute of Medical Sciences from August 2017 to August 2018. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 9 publications
4
13
0
1
Order By: Relevance
“…Conversely, low serum HDL levels did not affect the occurrence of cholesterol gallstones [109]. In addition, Wang et al showed that patients with increased plasma levels of cholesterol, triglycerides, HDL-c, LDL-c, and apolipoprotein B (APOB), also showed a significantly higher recurrence of gallstones compared to control patients [110], which was similar to those results found by Hayat et al, who showed that patients with gallstones had significantly higher plasma levels of triglycerides and HDL-c than the control patients [20]. All these data reaffirm the idea that high plasma levels of cholesterol and other lipids induce gallstone formation and, therefore, are heavily involved in the subsequent development of GBC.…”
Section: Nutritional and Lifestyle Aspects That Increase Susceptibili...supporting
confidence: 56%
See 1 more Smart Citation
“…Conversely, low serum HDL levels did not affect the occurrence of cholesterol gallstones [109]. In addition, Wang et al showed that patients with increased plasma levels of cholesterol, triglycerides, HDL-c, LDL-c, and apolipoprotein B (APOB), also showed a significantly higher recurrence of gallstones compared to control patients [110], which was similar to those results found by Hayat et al, who showed that patients with gallstones had significantly higher plasma levels of triglycerides and HDL-c than the control patients [20]. All these data reaffirm the idea that high plasma levels of cholesterol and other lipids induce gallstone formation and, therefore, are heavily involved in the subsequent development of GBC.…”
Section: Nutritional and Lifestyle Aspects That Increase Susceptibili...supporting
confidence: 56%
“…In those cases of multiple publications regarding the same topic, we consider only the most relevant studies. We identified one retrospective [17], five prospective [15,16,[18][19][20], nine meta-analyses [9,13,14,[21][22][23][24][25][26], eleven case-control [3,4,[27][28][29][30][31][32][33][34], and two Mendelian randomization [35,36] studies. Other additional sources of information consisted of experimental studies and review articles.…”
Section: Search and Selection Of Literaturementioning
confidence: 99%
“…Hypothetically, this can be achieved by lowering the a 1 parameter, which determines the amount of cholesterol transported with bile from the liver, but this change is difficult to achieve from the current state of knowledge. However, by using a TG-lowering diet, we can reduce the risk of gallstone formation 11 , 22 because it lowers the cholesterol absorption from the intestines in the form of chylomicrons (from the diet and from the membranes of dead enterocytes), owing to which the a 1 / a 2 ratio increases toward maintaining normal total cholesterol. The obtained results show the benefit of the reduction of enterohepatic circulation in obese people, which can be achieved in different ways: inhibition of ChA synthesis, increasing the duration of gall bladder emptying, reducing the amount of bile released during gall bladder contraction, and increasing its elimination with feces.…”
Section: Discussionmentioning
confidence: 99%
“…symptomatic gallstones), decreased physical activity, high BMI, cigarette smoking, and higher diastolic blood pressure increased the risk for clinical gallbladder disease [86]. Dyslipidemia is frequent in gallstone patients, who often have lower serum HDL and higher triglycerides levels, as compared to healthy control subjects [87]. A prior study involving inactive persons, marathoners and joggers found that physical activity levels were inversely associated with serum triglycerides [88].…”
Section: General Effects Of Physical Activity On the Gallbladder Hepatobiliary Tract And Systemic Pathwaysmentioning
confidence: 99%